Assessing traditional practices on post harvest facilities of copra processing for production efficiency based on the worker and the workplace - Barcena, Mykel Edrian L. (2012)
We can?t deny the abundance of natural resources in the Philippines in terms of agriculture. Agriculture has one of the leading roles in maintaining Philippines economic state through exportation, sustaining the needs and provision of jobs and livelihood of the Filipinos. Especially in the coconut industry, it has been approximately the source of livelihood of the one-third of the population based on a local statistics (DA, 2010) yet coconut farmers on the other hand remains in the poverty state. Addition to this, they also perform hazardous task due to lack of technological advancement, hence they perform them in manual labor. On the other hand, the farmers are clueless on how to improve their investments due to lack of researches in the field of agriculture. To answer these issues, this study performed to address the efficiency of the operation of copra processing in terms of the worker?s comfortability and the copra facility?s qualitative measurements. The ideal structural dimensions and perceived environmental conditions are based on the workers to address their comfortability. On the other hand, ideal area used in the copra processing facility and number of employees based on the number of nuts processed is also addressed. These solutions were based on studying the traditional practices of copra processing in Lupon, Davao Oriental. Addressing of efficiency issues might help the farmer?s change the perception of what life in the farm is and appreciate their livelihood in terms of financial and comfortability. The operation of the process of copra can produce reasonable output to uplift the industry and eventually for the farmers, do not need to migrate to urban areas
Thesis (BS Architecture) -- University of the Philippines Mindanao
Thesis (BS Architecture) -- University of the Philippines Mindanao, 2012